2021
DOI: 10.1111/jerd.12835
|View full text |Cite
|
Sign up to set email alerts
|

Stress distribution of a novel bundle fiber post with curved roots and oval canals

Abstract: Objective The aim of this study was to compare the stress distribution of teeth with curved and straight roots with oval and round canals restored with the bundle and conventional post systems. Material and methods Six three‐dimensional premolars were modeled with round and oval canals, and curved roots using the software. The bundle post and the round posts were modeled. All post models were placed on the canals. The models were subjected to 200 N oblique loading. The results were evaluated by von Mises stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…This design allows the bundle to be inserted after the adhesive and composite have been applied, resulting in a flexible approach to evenly distribute the bundle across the canal, especially in the case of irregularly shaped anatomy. Previous studies demonstrated that bundled fibre posts exhibited intracanal adhesion as well as fracture resistance comparable to that measured for solid fibre posts (Bitter et al, 2019;Kul et al, 2020;Sturm et al, 2021) but with more homogeneous stress distribution (Yanik & Turker, 2022). Root filled maxillary central incisors with mesial and distal class III cavities restored with direct composite demonstrated comparable fracture resistance to those restored with solid and bundled glass fibre posts, and increased resistance compared to those restored without posts (Comba et al, 2021).…”
Section: Postsmentioning
confidence: 62%
“…This design allows the bundle to be inserted after the adhesive and composite have been applied, resulting in a flexible approach to evenly distribute the bundle across the canal, especially in the case of irregularly shaped anatomy. Previous studies demonstrated that bundled fibre posts exhibited intracanal adhesion as well as fracture resistance comparable to that measured for solid fibre posts (Bitter et al, 2019;Kul et al, 2020;Sturm et al, 2021) but with more homogeneous stress distribution (Yanik & Turker, 2022). Root filled maxillary central incisors with mesial and distal class III cavities restored with direct composite demonstrated comparable fracture resistance to those restored with solid and bundled glass fibre posts, and increased resistance compared to those restored without posts (Comba et al, 2021).…”
Section: Postsmentioning
confidence: 62%
“…Periodontitis is an inflammatory disease characterized by the presence of inflammation of the supporting tissues of the teeth, resulting in attachment and alveolar bone destruction [ 2 ]. Despite extensive hard tissue loss, the teeth can survive and function with advanced restorative procedures [ 3 ]; however, the extensive periodontal loss may need tooth extraction. Therefore, periodontal health is crucial for the survival of the teeth.…”
Section: Introductionmentioning
confidence: 99%